Habitat Heterogeneity and Geographic Location as Major Drivers of Cerrado Small Mammal Diversity Across Multiple Spatial Scales - Carmignotto, Ana Paula; Pardini, Renata; de Vivo, Mario (Frontiers in Ecology and Evolution, 2022)
Cerrado is one of the global hotspots of biodiversity and non-volant small mammals represent a significant portion of this biome species richness (45%) and endemism (86%). Nevertheless, we still lack a comprehensive picture of small mammal diversity patterns and drivers throughout the Cerrado. Here we surveyed small mammals across 45 sites to address species richness, abundance and composition patterns and their drivers within and across sites, habitats and localities at the world’s most diverse tropical savanna. As hypothesized we found: 1- rich assemblages (12-21 species) characterized by few abundant and several intermediate level and rare species; dominated by oryzomyine and akodontine cricetid rodents, and thylamyine and marmosine within marsupials, each tribe showing distinct habitat requirements; 2- strong habitat selectivity, with assemblages composed of forest dwellers, savanna specialists, as well as grassland inhabitants; and 3- similar species richness (α-diversity) but high species turnover (β-diversity) across sites, habitats and localities, suggesting that horizontal stratification (within localities) and geographic location (across the Cerrado) are key for the diversity of small mammals in tropical savannas. So, habitat heterogeneity and geographic location can be inferred as the main factors shaping species richness, abundance and composition across the multiple spatial scales here analyzed. Moreover, we found that geographical distance as well as distance to neighbor biomes better explained species turnover, indicating landscape history and phylogenetic constraints as major determinants of small mammal diversity across the Cerrado, as also evidenced for plants and other animal groups. These data highlight the need to preserve the mosaic of habitats across different regions of the biome in order to conserve most of the Cerrado biodiversity.